OP29 The prevalence of congenital heart disease in the UK: a population-based register study. (2nd September 2014) - Best, KE; Draper, E; Kurinczuk, J; Stoianova, S; Tucker, D; Wellesley, D; Rankin, J
Abstract : Background: Congenital heart disease (CHD) is the most common group of structural congenital anomalies. Individuals with CHD require highly specialised health care, which may involve multiple complex and often life-saving surgeries. Current reforms of paediatric cardiology services in the UK are taking place to ensure adequate provisions are in place for children with CHD. Obtaining accurate information on trends and prevalence will aid health service planning in this area. Several studies have analysed trends in the prevalence of CHD, but few have investigated trends specific to CHD subtypes or severity categories. The aim of this study was to investigate the epidemiology of CHD, including trends in severe, moderate and mild CHD in the UK. Methods: All cases of CHD notified to six British Isles Network of Congenital Anomaly Registers between 1991–2010 formed this population-based study. Prevalence and 95% confidence intervals (CIs) were calculated as the number of cases (in live births, fetal deaths or terminations of pregnancy for fetal anomaly) per 10, 000 live and stillbirths. Relative risks (RRs) of CHD over time and by maternal age at delivery were estimated using multilevel Poisson models. Results: There were 19, 384 singleton cases of CHD among 3, 040, 952 total births. Excluding, 3777 (19.5%) cases with a chromosomal anomaly or genetic syndrome and 2370 (12.2%) with extra-cardiac anomalies, there were 13, 237 isolated cases. Of these, 7032 (53.1%, Prevalence = 23.1, 95% CI: 22.6–23.7 per 10, 000 total births) were mild, 3389 (25.6%, Prevalence = 11.1, 95% CI: 10.8–11.5) were moderate and 1145 (8.7%, Prevalence = 3.8, 95% CI: 3.6–4.0) were severe CHD. There were no significant trends in moderate (RR=1.02, 95% CI: 0.99–1.04; p = 0.195) or severe CHD (RR=1.01, 95% CI: 1.00–1.03; p = 0.065), but there was a significant increase in the prevalence of mild CHD (RR=1.05, 95% CI: 1.01–1.10; p = 0.029). The trends over time remained relatively unchanged after adjustment for maternal age at delivery. Compared to women aged 20–29, the risk of mild CHD was significantly increased in the offspring of women aged ≥35 (RR=1.10, 95% CI: 1.02–1.19; p = 0.016) and the risk of severe CHD was significantly greater in the offspring of women aged 30–34 (RR=0.80, 95% CI: 0.65–0.98; p = 0.030). There were no associations in any other maternal age category. Conclusion: There were no significant trends in the prevalence of severe or moderate CHD but there was evidence of an increase in mild CHD prevalence, which existed after adjustment for maternal age at delivery. This information is important for healthcare planning.